STUDI ETNOBIOLOGI TANAMAN PADI - Eladisa Ganjari, Leo (Widya Warta, 2020)
The rice crop has long been known by the world community, specifically in Indonesia.Â  Knowledge of rice plants that support cultivation and utilization has been initially passed down through generations. This research aimed to explore the cultural potential (ETNO) related to the biology of rice plants. The results showed the existence of ethnobiological activity in Indonesia. It was reflected in the culture (ETNO) ceremony or traditions. It turned out that in Indonesia, there were many local rice fields with ecotourism (agroecosystems). The presence of culture (ETNO) that continues to be done will support the existence of rice crop biodiversity. Thus, a rice-plant ethnobiology study needs to be developed to support cultural preservation and nature preservation.